DNA microarray revealed and RNAi plants confirmed key genes conferring low Cd accumulation in barley grains. Issue 1 (December 2015) - Sun, Hongyan; Chen, Zhong-Hua; Chen, Fei; Xie, Lupeng; Zhang, Guoping; Vincze, Eva; Wu, Feibo
Abstract Background Understanding the mechanism of low Cd accumulation in crops is crucial for sustainable safe food production in Cd-contaminated soils. Results Confocal microscopy, atomic absorption spectrometry, gas exchange and chlorophyll fluorescence analyses revealed a distinct difference in Cd accumulation and tolerance between the two contrasting barley genotypes: W6nk2 (a low-grain-Cd-accumulating and Cd-sensitive genotype) and Zhenong8 (a high-grain-Cd-accumulating and tolerant genotype). A DNA microarray analysis detected large-scale changes of gene expression in response to Cd stress with a substantial difference between the two genotypes. Cd stress led to higher expression of genes involved in transport, carbohydrate metabolism and signal transduction in the low-grain-Cd-accumulating genotype. Novel transporter genes such as zinc transporter genes were identified as being associated with low Cd accumulation. Quantitative RT-PCR confirmed our microarray data. Furthermore, suppression of the zinc transporter genesHvZIP3 andHvZIP8 by RNAi silencing showed increased Cd accumulation and reduced Zn and Mn concentrations in barley grains. Thus, HvZIP3 andHvZIP8 could be candidate genes related to low-grain-Cd-accumulation. Conclusion Novel transporter genes such asHvZIP3 andHvZIP8 were identified as being associated with low-grain-Cd-accumulation. In addition to advancing academic knowledge, our findings may also result in potential economic benefits for molecular breeding of low Cd accumulating barley and other crops.